2018
DOI: 10.2174/1381612824666180717155953
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase and the Skin in Health and Disease

Abstract: The skin is often introduced as the largest organ of the human body which - being uniquely exposed to external stress - faces several types of challenges, from physical, chemical, biological, and immunological origin. Therefore, the skin is also a site where inflammation, oxidative stress and cellular damage occurs regularly. Heme oxygenase (HO), primarily functioning in the catabolism of heme, is a very important cytoprotective enzyme that has antioxidant, anti-inflammatory and anti-apoptotic properties. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The skin acts as a barrier to prevent water loss and resist external insults . Skin trauma will destroy the barrier function of the skin, weaken normal functions and even induce skin tumors . Although most skin traumas are self‐healing, promoting the closure of skin wound by pharmacological means is beneficial to shortening the course of the wound, reducing the risk of systemic infection and satisfying the cosmetic needs of the patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin acts as a barrier to prevent water loss and resist external insults . Skin trauma will destroy the barrier function of the skin, weaken normal functions and even induce skin tumors . Although most skin traumas are self‐healing, promoting the closure of skin wound by pharmacological means is beneficial to shortening the course of the wound, reducing the risk of systemic infection and satisfying the cosmetic needs of the patients .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Skin trauma will destroy the barrier function of the skin, weaken normal functions and even induce skin tumors. [3] Although most skin traumas are self-healing, promoting the closure of skin wound by pharmacological means is | 777 XU et al…”
mentioning
confidence: 99%
“…In skin, heme oxygenases are cytoprotective against reactive oxygen species generated during normal physiological processes, and they limit oxidative stress following exposure to environmental assaults (Szabo et al, 2018). Previously, we have demonstrated that bites of L. longipalpis sand flies induce NFE2L2-dependent production of HO-1 in human skin that was attributed to the effect of saliva (Luz et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…GSH-Px, another enzyme responsible for H 2 O 2 reduction, oxidizes reduced glutathione (GSH) to glutathione disulfide, converts peroxides and hydroxyl radicals into non-toxic forms, and then reduces them to GSH by glutathione reductase [14]. Redox homeostasis of the cell is also protected by its complex endogenous antioxidant enzymes such as heme oxygenase and heme-containing peroxidases [15], and non-enzymatic compounds like glutathione, proteins (ferritin, transferrin, ceruloplasmin, and even albumin) and low-molecular weight scavengers, like uric acid, coenzyme Q10, and lipoic acid [6,16].…”
Section: Introductionmentioning
confidence: 99%